PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAME TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL SISWA KELAS IV SEKOLAH DASAR NEGERI 73 PEKANBARU - Zulhefa Maryam; Harmizi '; Erlisnawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Background problem in this study is the low student learning outcomes with an average value of 61.2. This study aims untukmeningkatkan learning outcomes IPS Elementary School fourth grade students 73 Pekanbaru with the implementation of cooperative learning model type Teams Games Tournament. The research design was digunakanya classroom action research (PTK) are conducted in two cycles. Each cycle consisted of four meetings and one-time delivery of content meeting daily tests. Research implemented in March and April with a number of 21 students consisting of 11 male and 10 female. Classroom action research in order to succeed, the researchers set the stage that action planning, action, observation and reflection. As for the data pengumupulan instrument of observation and tests of learning outcomes. Based on the research that the learning outcome gained an average of 61.2 after measures implemented in the first cycle learning outcomes of students increased to 68.1. An increase student learning outcomes of prior actions to the first cycle of 6.9. After the action on the second cycle of the average student learning outcomes increased again to 75 with an increase from the first cycle to the second cycle of 6.9. While the increase from before action to the second cycle of 13.8. Activity teacher meetings I 60% by the middle category, meetings with category III 70% good, 85% VI meeting with a good category VIII meeting 95% with very good category. While the activities of students at the meeting of the first meeting with category 58.3%, 66.7% III meeting with the middle category, 83.3% VI meeting with a good category VIII Meeting 91.7% with very good category. From this research, the conclusion that by implementing cooperative learning model type Teams Games Tournament (TGT) may improve learning outcomes IPS Elementary School fourth grade students 73 Pekanbaru.Keywords: Cooperative Learning Model Teams Games Tournament (TGT) and Learning Outcomes